EVALUASI DAMPAK KEBIJAKAN PENINGKATAN MINAT DAN GEMAR MEMBACA TERHADAP MASYARAKAT KOTA JAMBI OLEH DINAS PERPUSTAKAAN DAN ARSIP DAERAH PROVINSI JAMBI - Tiara, Winanda (JISIP UNJA (Jurnal Ilmu Sosial Ilmu Politik Universitas Jambi), 2018)
The Regional Library and Archive Office of Jambi Province is the Regional Government Work Unit of the Jambi Province which has a role in increasing interest and fond of reading the community in Jambi Province. This study aims to evaluate the impact of interest and interest in reading policies carried out by the Department of Library and Archives of Jambi Province towards the people of Jambi Province, especially the people of Jambi City. This study uses Rossi's, Islamy's theory of evaluating the impact of Leo Agustino's policies and theories regarding policy evaluation criteria consisting of apparatus, institutional, financial, infrastructure and technology, and supporting regulations. This study used a descriptive qualitative research method and interviews were conducted with the section head of civilization reading development, head of the Jambi City institutional and community section who visited the Regional Library and Archive Office of Jambi Province. The results showed that the Regional Library and Archives Office of Jambi Province in carrying out the improvement policy and fond of reading experienced a change, namely the increased reading interest of the people of Jambi City, but the change was not as expected and had not happened significantly.